Perancangan dan Implementasi Sistem Keamanan Pada Brankas Menggunakan Paralel Fingerprint dan Keypad Berbasis Arduino - Al Rafif, Muhammad Roid; Paniran, Paniran; Wiriasto, Giri Wahyu (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
Safe security plays an important role in protecting valuable assets from unauthorized access. Designing and implementing a security system on a safe using a parallel combination of two fingerprint sensors and a keypad. This is to increase the level of security by ensuring that both fingerprint sensors verify the fingerprint simultaneously before the user enters the code via the keypad to open the safe. The system controller uses an Arduino Mega as the main microcontroller, which connects two fingerprint sensors, a 4x4 keypad, a 16x2 LCD to display information, a 1 channel relay to drive the solenoid door lock as an actuator, and a buzzer as a warning indicator. The system testing scenario consists of three stages, namely, Electronic relay testing is carried out to ensure that the relay functions properly in controlling the solenoid door lock, so that the locking and opening mechanisms of the safe can run according to command. Testing on parallel fingerprints aims to evaluate the accuracy and speed of the sensor in reading two fingerprints simultaneously and ensuring that only registered fingerprints can access the system. Furthermore, keypad testing is carried out to verify the accuracy in reading the access code and testing the warning system in the event of an input error or unauthorized access attempt. The implementation results show that the system has a fingerprint authentication success rate of 98%, with an average response time of 1.2 seconds. The keypad reading accuracy reaches 99%, while the safe locking and opening mechanism functions with a 100% success rate. With these results, the developed system is proven to work reliably and provide additional protection compared to conventional methods.